Speech Etiquette and Its Psychological Impact on Understanding Internet News - Akimova, Nataliia (East European Journal of Psycholinguistics, 2017)
The paper is focused on understanding features of Internet news. Among the main methods of analysis applied are descriptive text analysis, linguocultural and concept text analysis, descriptive introspection and modeling, method of semantic and pragmatic interpretations, contextual observation. The author emphasizes that specific characteristics of Internet news should be considered in studying their understanding process. Internet news differ from print news by lack of censorship, weak dependence on the publication format, hypertext, interactivity, electronic form that allow simplifying the printing process, saving time, collective authorship, the possibility of archiving and electronic search, the possibility of permanent access from anywhere in the world, multimedia, unlimited print run and low cost, fragmentation. These new technical features create the potential for introducing various communicative phenomena, in particular personalization, violation of linguistic rules, simplification, use of jargon, invectives and terms that forms a specific Internet news speech etiquette. Verbs in the third form of a plural, often not calling the subject of action, or calling it only formally, i.e. as a metonymy (for example: “power”) or as a name without referent, are typical for Internet news etiquette. Such speech etiquette of the Internet news significantly complicates their content understanding. Besides same values, attitudes and pattern are imposed on readers using confusing utterances. Psychological features of the Internet news’ speech etiquette impact on understanding are represented in the text understanding model proposed in this article. References Akіmova, N. (2014). Internet-kommunikatsiya: psikholingvisticheskiy analiz: Monografiya [Internet-communication: Psycholinguistic Analysis]. Saarbryúkken : LAP LAMBERT Academic Publishing. Akіmova, N. Movlennevі devіacіyi u movі ukraїns’kih іnternet-ZMІ: tendencіja movy epokhy chy zasіb manіpuliuvannia [Speech deviation in the language of Ukrainian online media: the tendency of epoch’s language or means of manipulation]. Retrieved from http://mentalnist-2016.blogspot.com/p/blog-page_49.html. Akіmova, N. (2016). Frahmentarnist’ novynnoyi internet-komunikatsiyi yak faktor, shcho uskladnyuye yiyi rozuminnya [Fragmentation of the Internet news communication as a factor that complicates its understanding]. Psykholinhvistyka, 20(2), 12-20. Batmanova, S. (2004). Setevyye SMI: faktory efektivnosti [Network mass media: factors of effectiveness]. Extended abstract of candidate’s thesis. Voronezh. BTSRYA – Kuznetsov, S.A. (Eds.). (2009) Bol’shoj tolkovyi slovar’ russkogo jazyka [Big Dictionary of Russian]. S.-Petersburg: Norint. Dvoynina Ye. (2010). Rechevaya manipulyatsiya v internet-diskurse (na materiale russko- i angloyazychnykh novostnykh saytov) [Speech manipulation in Internet discourse (on the basis of Russian and English-language news sites)]. Extended abstract of candidate’s thesis. Saratov. Il’ina I. Problemy izucheniya i vospriyatiya giperteksta v mul’timediynoy srede internet [Problems of studying and perception of hypertext in the multimedia environment of the Internet]. Retrieved from www.ipk.ru. Karamysheva R. (2009). Rehistrovo-zhanrovi kharakterystyky povidomlen’ pro stykhiyni lykha na ukrayinomovnykh ta anhlomovnykh internet-saytakh [The register and genre characteristics of reports of natural disasters in Ukrainian and English web sites]. Linhvistychni Studiyi, 18, 167–173. Koval’chukova M. (2009). Novostnoy anons v seti internet kak rechevoy zhanr diskursa SMI [News announcement in the Internet as a speech genre of the discourse of the media]. Extended abstract of candidate’s thesis. Izhevsk. Kolomiyets’ S., Kulyezniova S. (2012). Zhanrovo-styliova dominanta v perekladi tekstiv internet-dyskursu [Genre-style dominant in the translation of texts of Internet discourse]. Funktsyonalnaya Lyngvistika, 3, 176-284. Kulakova V. (2007). Internet v sisteme sredstv massovoy informatsii Tadzhikistana [Internet in the system of mass media of Tajikistan]. Extended abstract of candidate’s thesis. Dushanbe. Filatova, O. G. (2004) Internet kak mass-media [Internet as a mass media]. Aktual’nye Problemy Teorii Kommunikatsii, 232-240. Sources RBK – RosBiznesKonsalting – novosti, akcii, kursy valjut, pogoda, dollar, evro [RosBusinessConsulting – News, Stocks, Exchange rate, weather, dollar, euro]. Retrieved from http://www.rbc.ru/.